2020
DOI: 10.1186/s40779-020-0233-6
|View full text |Cite
|
Sign up to set email alerts
|

A rapid advice guideline for the diagnosis and treatment of 2019 novel coronavirus (2019-nCoV) infected pneumonia (standard version)

Abstract: In December 2019, a new type viral pneumonia cases occurred in Wuhan, Hubei Province; and then named "2019 novel coronavirus (2019-nCoV)" by the World Health Organization (WHO) on 12 January 2020. For it is a never been experienced respiratory disease before and with infection ability widely and quickly, it attracted the world's attention but without treatment and control manual. For the request from frontline clinicians and public health professionals of 2019-nCoV infected pneumonia management, an evidence-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
2,018
5
151

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,926 publications
(2,297 citation statements)
references
References 15 publications
35
2,018
5
151
Order By: Relevance
“…So far, this disease has rapidly spread from Wuhan to China's other areas, and 66 countries. And then, clustered cases and confirmed cases without a history of travel to Wuhan emerged as the advancing of this disease [9] . In addition, confirmed cases without clear exposure to the seafood market of Wuhan have been spread in many foreign countries [10] .…”
Section: Scope Of the Covid-19 Infection Outbreakmentioning
confidence: 91%
See 3 more Smart Citations
“…So far, this disease has rapidly spread from Wuhan to China's other areas, and 66 countries. And then, clustered cases and confirmed cases without a history of travel to Wuhan emerged as the advancing of this disease [9] . In addition, confirmed cases without clear exposure to the seafood market of Wuhan have been spread in many foreign countries [10] .…”
Section: Scope Of the Covid-19 Infection Outbreakmentioning
confidence: 91%
“…SARS-CoV-2 is the seventh member of the family coronaviruses, which is the beta-CoV with over 70% similarity in genetic sequence to SRAS-nCoV [16]. Like SARS-CoV, MERS-CoV, and many other coronaviruses, SARS-CoV-2 likely originated in bats, but it requires further confirmation whether pneumonia infected by the SARS-CoV-2 is transmitted directly from bats or through an intermediate host [9,17,18] .Recent research has found that the virus is 96% identical at the whole-genome level to a bat coronavirus, which means bats is the most possible host of the SARS-CoV-2 [17,18] . Also, Ji and colleagues [19] demonstrated that snack as possible virus reservoir for human infection.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Special attention and efforts to protect or reduce transmission should be applied in susceptible populations including children, health care providers, and elderly people. A guideline was published for the medical staff, healthcare providers, and, public health individuals and researchers who are interested in the 2019-nCoV [29]. The early death cases of COVID-19 outbreak occurred primarily in elderly people, possibly due to a weak immune system that permits faster progression of viral infection [8,12].…”
Section: Future Directions To Control the Spread Of The Diseasementioning
confidence: 99%